(untitled) (Ameghiniana, 2013)
Mammal remains from sediments referable to the Holocene and probably to the late Pleistocene in the southeast of Buenos Aires province were analyzed. 650 remains were recovered and assigned to 24 taxa. Based on the stratigraphic distribution, the frecuency analysis and the biological characteristics of the species, 2 faunal groups were identified: B (lower levels) and A (upper levels). It is concluded that : 1- The fauna from the B group is related with environrnental conditions that were more arid than the present ones and with lower mean temperatures. 2- The fauna from the A group is related with environmental conditions similar to the present ones. 3- A variation, from the bottom to the top of the profile can be observed: the fauna related with arid to semiarid conditions is progressively replaced and/or accompained by more humid condition indicators. This transitional faune lasted at least until the period 1.730-1.220 radiocarbon years B. P.